A landscape in transition: an historical perspective on a Spanish latifundist farm - Pérez, A S; Remmers, G G A (Agriculture, ecosystems & environment, 1997)
An agricultural landscape, as a social construction, is not static, but a reflection of the balance of social forces which influence the way in which the natural resources of the site are combined. To understand and evaluate the current configuration of a landscape, and to define and understand criteria according to which a future landscape may be designed, it is necessary to analyse its historical construction. In this paper we follow these steps, taking as a point of reference a farm in one of the most important agricultural regions of Spain, the Guadalquivir river valley in Andalucla. This region stands out for its high production potential, social inequity and environmental degradation. The paper describes global changes in the use of the land in this river valley over the past 3 centuries, and uses aerial photographs from 1956 and 1990 to outline changes on the 1150-ha Los Humosos farm, recently granted to a co-operative of land labourers after years of struggle for land. Through this change in tenure the criteria 'control' and 'distribution of benefits' are achieved. Nine other criteria derived from the historical analysis were used to compare four different farm design scenarios through multi-criteria programming, which was preceded by an assessment of the biogeophysical characteristics of the land. However, this appeared to be insufficient to cope with essential criteria such as landscape architecture and biodiversity, because minor landscape elements were neglected which are important starters for the design of an ecological infrastructure. Water, a problematic resource in Mediterranean agriculture, paradoxically turned out to be an important characteristic of these landscape elements. From historical, ecological and social perspectives, new proposals for farm landscape design must necessarily and radically break with the recent past. It appears, however, that to produce agricultural landscapes of quality in the Guadalquivir river valley would involve tough social struggle, that nonetheless is found to use the margins left over by the dominant socio-economic, cultural and political structures. Finally, an agro-ecological option is proposed as a transitional design
Keywords: ecological agriculture; History; land labourers; landscape; Mediterranean; Spain; water